2011
DOI: 10.1212/wnl.0b013e31821f4636
|View full text |Cite
|
Sign up to set email alerts
|

Problem neurology residents

Abstract: The prevalence of problem residents in neurology is similar to other disciplines, and various resources are available to remediate them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…(Yates and James 2006;Tabby et al 2011;Steinert 2013;Winston et al 2014). In this paper we will use the term ''struggler'' to mean a student who progresses with difficulty, which may or may not involve a strenuous effort.…”
Section: Introductionmentioning
confidence: 99%
“…(Yates and James 2006;Tabby et al 2011;Steinert 2013;Winston et al 2014). In this paper we will use the term ''struggler'' to mean a student who progresses with difficulty, which may or may not involve a strenuous effort.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In a survey, pediatrics program directors reported that residents terminated after failed remediation were significantly more likely to have deficiencies in ICS and professionalism, 8 while neurology program directors noted that the most prevalent issue for ''problem neurology residents'' was professionalism, as demonstrated by inappropriate interactions with colleagues and staff. 9 Among program directors in emergency medicine, 80% noted that deficiencies in professionalism were harder to remediate than deficiencies in other core competencies. 10 Clinical skills examination scores for Canadian medical students showed a predictive relationship between students who scored poorly on communication and future complaints in their medical practice, with students in the bottom quartile accounting for a significantly higher percentage of patient complaints.…”
Section: The Problemmentioning
confidence: 99%
“…often. 3 The difference in the frequency of MK deficits may be due to underlying differences in the population of neurology and pediatrics residents, or it may be due to differences in the requirements for competence or assessment of MK in neurology and pediatrics residencies. With the exception of MK and SBP, which was not measured in the neurology study, the patterns seen in the study of neurology residents needing remediation were similar to those found in this study of pediatrics residents requiring remediation.…”
Section: Deficiencies In Core Competencies Among Residents Requiring mentioning
confidence: 99%
“…However, few studies have addressed the impact of the competencies on remediation, the process of correcting knowledge deficits or other deficiencies in trainees with the ultimate goal of producing well-trained and competent attending physicians. 3,4 Remediation was recently described as occurring in 3 steps: (1) the identification of deficiencies in an individual's performance; (2) an attempt to provide remedial education to that individual; and (3) reassessment to determine the impact of the education. 5 This conceptual model of remediation was used to develop a survey of pediatrics residency program directors in order to study remediation Background The 6 competencies defined by the Accreditation Council for Graduate Medical Education provide the framework of assessment for trainees in the US graduate medical education system, but few studies have investigated their impact on remediation.…”
Section: Introductionmentioning
confidence: 99%